The effect of substrate on cryopreservation of the mycelium of wood decay basidiomycetes (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: How can the pure cultures of basidiomycetes from the IBK Mushroom Culture Collection be preserved for a long time? Location: IBK Mushroom Culture Collection of the M.G. Kholodny Institute of Botany, National Academy of Sciences of Ukraine Materials and methods: standard mycological methods of cultivation of the pure culture of fungi Nomenclature: https://www.mycobank.org/ Results: Culture collections are essential for characterizing and studying fungal species; however, the primary goal of these collections remains the preservation of fungal species diversity and their gene pool. The IBK Mushroom Culture Collection is the largest official specialized culture collection of macromycetes in Ukraine, preserving more than 1,500 strains of edible and medicinal mushrooms. Since there is a need for a reliable method for longterm storage of pure cultures of fungi, the cryopreservation of nine different strains of five wood decay fungi was investigated in this work. Wood-decay fungi have various applications in diverse fields. In particular, studied in this work, Fomitopsis pinicola 361, two strains of Ganoderma tsugae 1848 and 2566, three strains of Laricifomes officinalis 2497, 2498, and 5004, Pleurotus ostreatus 297, and two strains of Schizophyllum commune 1768 and 1769 are valuable species of wood decay fungi due to their contents of various biologically active compounds. They have diverse applications in pharmacology, biotechnology, and bioremediation due to their enzyme activities. According to this, these species should not change during long-term storage; however, it is known that during long-term storage of cultures on culture medium, certain changes in the activity of enzymes may occur. Storage at low temperatures protects the culture from those changes. Barley, pearl barley, wheat, and four versions of the wooden sticks were studied as substrates for the mycelium storage at a 10% solution of glycerol at low temperatures. Covered by mycelium substrates were stored for one year at – 80℃. After this period, the recovery of mycelium growth was studied on the Petri dishes with glucoseyeast- peptone agar medium at 26 ℃. All studied strains revived and grew after storage. Such research was performed for the first time for F. pinicola and G. tsugae. The obtained results demonstrate a better revival of the mycelium on the grains as a substrate. However, the strains F. pinicola 361 and S. commune 1769 are an exception due to their better growth rate after storing on the wooden sticks. The advantages of the described method of storing pure cultures of the fungal species are no need for constant reseeding, which reduces the risk of contamination and excludes the possibility of accumulation of genetic changes.
Keywords: biodiversity, cryoconservation, filamentous fungi, long-term storage, viability, wood decay basidiomycetes